EVALUATION FOR MOTHERS' PRACTICES TOWARDS CARING FOR THEIR CHILDREN WITH EPILEPSY - Israa Musa Jaafar Sadiq; Professor Dr. Shukriya Shadhan Al-Ogaili (Journal of Medical Genetics and Clinical Biology, 2024)
Background: Epilepsy is classified as a neurological condition impacting the nervous system, characterized by spontaneous seizures that occur on a regular basis with varying occurrence and severity. The study aimed to assess the level of mother’s practices regarding epileptic among children in Babylon province. Materials and methods: This descriptive and analytical cross-sectional study was conducted at Babil Teaching Hospital for Maternity and Children's EEG unit, emergency wards, and neurological consultation ward. A purposive sample of 100 mothers was selected. Closed-ended questions were asked to each woman in direct interviews. The study was conducted for period from November 2023 to February 2024 is the study period. Results: The results found that 35.0% of mothers belonging to age group (29-34 years). The results found that the highest percentage was 71% of those with moderate practice, followed by 17% with poor practice, and 12% with good practice. Also, the results report that the mothers whom were sufficient family income, live in urban and have higher education level, were with the better practices score (P. value <0.05). Conclusion: The study concluded that the majority of mothers in Babil Governorate have moderate practices of epilepsy. The results also revealed that sufficient family income, mothers living in urban areas, and higher education were associated with a good degree of practices. Educating the public about epilepsy through the mass media could go a long way in reducing the morbidity and mortality associated with this problem